COMPARATIVE ANALYSIS OF THE IMPLEMENTATION OF INTERNET FINANCIAL REPORTING BY ZAKAT MANAGEMENT ORGANIZATIONS (OPZ) IN INDONESIA - Basyasyatul Hanafiyah; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of this study was to determine the differences of Internet Financial Reporting (IFR) index between Lembaga Amil Zakat Nasional (LAZNAS)  and Badan Amil Zakat Nasional Provinsi (BAZNASPROV) in Indonesia. This research uses a quantitative approach with an independent sample t-test. The population in this study is the official website of LAZNAS and BAZNASPROV in Indonesia. Sample selection using purposive sampling technique with two criteria. The website have to be can accessed properly, furthermore LAZNAS and BAZNASPROV have been inaugurated for more than 2 years. The data used is secondary data. Data collection was obtained from the official websites of LAZNAS and BAZNASPROV in Indonesia. The results of this study indicate that there is no significant difference in the IFR index between LAZNAS and BAZNASPROV. Based on the four IFR components used, one and only component showed significant difference is technology used. However, the results obtained that between LAZNAS and BAZNASPROV still do not provide maximum on internet financial reporting yet.Keywords: Internet Financial Reporting, LAZNAS, BAZNASPROV